Understanding the perception of society towards ‘pengkid’: effective solutions - Abdul Rahim, Adibah (2012)
‘Pengkid’ is a term used to refer to a woman with masculine appearances and is prone to same gender sexual orientation. The ‘pengkid’ pictures the identity that contradicts with their biological nature as well as their moral and social values. This inverse culture obviously contradicts with a human nature, and it might be identified as a gender crisis. It might also affect Muslims’ faith and brings harms to the society. ‘Pengkid’ has been prohibited by the National Council of Fatwa (Majlis Fatwa Kebangsaan), but the problem is still seriously spreading in the society. By using both quantitative and qualitative methodologies, this paper aims at identifying physical and behavioural indicators of ‘pengkid’. In addition, the paper aims to identify contributing factors that lead to the spread of ‘pengkid’, as well as studying the relationship between pengkid and their level of religious understanding. This paper also provides suggestions and plans of actions in order to curb the increasing problems of ‘pengkid’ in society.